Phylogenetic, genetic, and phenotypic diversity of Pseudomonas syringae pv. syringae strains isolated from citrus blast and black pit in Tunisia. (7th August 2020) - Abdellatif, Emna; Kałużna, Monika; Ferrante, Patrizia; Scortichini, Marco; Bahri, Bochra; Janse, Jaap D.; van Vaerenberg, Johan; Baeyen, Steve; Sobiczewski, Piotr; Rhouma, Ali
Abstract: Citrus blast and black pit caused by Pseudomonas syringae pv. syringae (Pss) is the only bacterial disease reported in Tunisian Citrus orchards. The phylogenetic relationship between Pss strains was studied based on multilocus sequence analysis (MLSA), using partial sequences of housekeeping genes rpoD, rpoB, gyrB, cts, and pfk for 14 representative Pss Citrus strains, including the reference strain LMG5496. The MLSA revealed that the studied Tunisian Citrus strains are closely related to LMG5496 and cluster in phylogroup 02. Based on the cts gene, the majority of Citrus strains clustered in clades "a" and "b". However, five strains were placed in a newly defined clade "g". We describe the presence of six different type III secreted effectors (T3SEs). These were found with frequencies of 100% for the effector hopAN1 and the helper hrpK1, 65% for hopT1‐2, and 14% for hopN1, hopR1, and hopQ1‐2 . Investigation of copper resistance showed that 67% of our Pss Citrus strains from Tunisia are resistant to copper sulphate in vitro, and the copper resistance genes copABCDR were detected in 23% of the strains. Our results present new data concerning the genetic diversity and phylogeny, presence of T3SEs, and copper resistance within the Pss populations that affect Citrus in Tunisia. Abstract : Multilocus sequence analysis of Pseudomonas syringae pv. syringae, causal agent of citrus blast and black pit, examined the presence of type III secreted effectors and copper resistance genes copABCDR .